Next word, better word : the craft of writing poetry - Dobyns, Stephen (New York, United States : Palgrave Macmillan, 2011)
"This accessible writer's guide provides a helpful framework for creating poetry and navigates contemporary concerns and practices. Stephen Dobyns, author of the classic book on the beauty of poetry, Best Words, Best Order, moves into new terrain in this remarkable book. Bringing years of experience to bear on issues such as subject matter, the mechanics of poetry, and the revision process, Dobyns explores the complex relationship between writers and their work. From Philip Larkin to Pablo Neruda to William Butler Yeats, every chapter reveals useful lessons in these renowned poets' work. Both enlightening and encouraging, Next Word, Better Word demystifies a subtle art form and shows writers how to overcome obstacles in the creative process"--Provided by publisher
Includes bibliographical references and index
Keywords: Poetry -- Authorship; Creation (Literary, artistic, etc.); Poetics